Simulation and measurement of ultrathin glass residual stress. (13th September 2022) - Tong, Lianjie; Liu, Shimin; Sun, Yaming; Gu, Jianmin; Xu, Shiqing
Abstract: Accurate simulation and measurement of the residual stress are pressing needs in ultrathin glass (UTG) industrial stable production. Herein, the heat transfer in an annealing lehr and the residual stresses at different positions along the width of the UTG ribbon were simulated by the finite element method and measured via the Vickers indentation. The residual stresses at 400 and 600 mm to the edge were large, which caused serious production loss. Besides, we conducted molecular dynamics (MD) simulation to reveal the mechanism for residual stress formation. During UTG cooling, the cooling rate of the core is slower than that of the surface. Due to the influence of the relaxation process, the latter would hinder the former's R–O (where R is Na, Mg, Ca, Al, or Si) length contraction, implying that the surface would generate residual compressive stress. The temperature difference between them increases as the cooling rate grows, leading to the residual stress increase. Finally, based on revealing the formation principle of residual stress by MD, the edge electric heatings were set in zone B, and the residual stresses at 400 and 600 mm to the edge are reduced.